Contributions to the taxonomy of the Normanellidae (Copepoda, Harpacticoida): description of a new genus from the Brazilian continental shelf and re-assignment of Pseudocletodes vararensis Scott & Scott, 1893 (ex Nannopodidae) - Kihara, Terue Cristina; Huys, Rony (Zootaxa, 2009)
A new genus and species of Normanellidae (Copepoda, Harpacticoida), Paranaiara inajae gen. et sp. nov., is described from the continental shelf off the northern coast of São Paulo State, Brazil. The new genus differs from the type genus Normanella Brady, 1880 and Sagamiella Lee & Huys, 1999 in its presence of lamelliform caudal rami, a maxillulary endopod represented by 2 setae, an unarmed maxillipedal syncoxa, and reduced setation on P2 enp-2 (without outer spine) and P3 enp-2 (with only 2 inner setae). All these apomorphic character states are shared with the genus Pseudocletodes Scott & Scott, 1893, formerly placed in the family Nannopodidae (ex Huntemanniidae) and here assigned to the Normanellidae. Pseudocletodes can be differentiated from Paranaiara by the loss of the P1 endopod and of the inner seta on P2–P4 enp-1, the presence of only 2 inner setae on P2 enp-2 (instead of 3) and only 1 inner seta on P4 exp-3 (instead of 2), the presence of a second inner seta on P4 enp-2 (instead of 1), the morphology of the fifth pair of legs which are not medially fused and have only 3 endopodal elements (instead of 4) in the male, and the well developed caudal ramus seta V (instead of rudimentary). It is postulated that prehensility of the P1 endopod was secondarily lost in the common ancestor of Paranaiara and Pseudocletodes. An updated family diagnosis of the Normanellidae and a dichotomous identification key to the 22 currently valid species are presented.